OS 06-04 CHANGES IN GENE EXPRESSION PATHWAYS PREDICT DELAYED SODIUM EXCRETION DURING SALINE INFUSION. (September 2016) - Hunt, Steven; Hopkins, Paul; Nanjee, Nazeem; Schwander, Karen; Kohan, Donald; Rao, D. C.; Williams, Gordon
Abstract : Objective: Identify the earliest hormonal, electrolyte and gene expression responses to a saline infusion before compensatory mechanisms are activated and relate these responses to delayed sodium excretion. Design and method: 233 normotensive subjects with a strong positive family history of hypertension, ages 21–65, were studied on a low sodium diet before, during and after a 2-hour, 2-liter saline infusion. Plasma and urine hormones of the renin-angiotensin-aldosterone, catecholamine, uric acid, kallikrein, and cortisol pathways, microalbumin, and urine and plasma electrolytes were measured. Plasma was collected at 0, 5, 15, 30 and 60 minutes; urine at 0, 1, 2, 4, and 6 hours; blood pressures every 15 minutes; and arterial stiffness at baseline. RNA sequencing of baseline and 1-hour WBC samples (51, 041 transcripts) and 247, 451 genotypes from the rare variant exome chip were analyzed by Edge2 software and PLINK. Urinary sodium excretion at 2 hours was divided into tertiles. Subjects were classified as early, average and delayed sodium excretors. Results: Upon completion of the infusion, urinary calcium (p < 0.001), uric acid (p < 0.001), cortisol (p = 0.003), angiotensinogen (p = 0.009), and microalbumin (p = 0.001) were significantly decreased in the delayed excretors. PRA (p < 0.001), plasma renin concentration (p < 0.001), and plasma aldosterone (p < 0.001) were significantly increased at all time points. Interactions of early versus delayed urinary Na excretion with PRA, renin concentration, uric acid, microalbumin, and calcium excretion were significant. Genes differentially expressed between early and delayed sodium excretion subjects included AHNAK, LCP1, PSAP, RYR2, ASTN2-AS1, LIMCH1, HMCN1, ACOXL, SGCA, PTGR1, FLNA and BIK at p < 2.9X10 –5, or an FDR of 10%. Cardiac or endothelial calcium, collagen, and contraction pathways were represented by many of these genes. Conclusions: Earliest changes in gene expression were genes related to calcium pathway genes involved with stretch and contraction of the heart or vascular system. These changes were strongly related to how fast a salt load could be excreted.